Behçet's disease - A national casuistic - Crespo, Jorge (1997)
Since january 1993 a National Study Group from Por tugal, gathers physicians from different specialitles, that share a common interest in this clinical syndrome. As a result, it was posslble to obtain a population of 241 patientsfrom the whole country (121 males/ 120 females, average age = 3 6 ± 11,8 years), with diagnostic crlteria as deflned by the ISGBD. The following conclusions were reached: BD is a condition of early onset, usually between the 2nd and 4th decades of life (average age of onset from ftrst symptom = 25,8 ± 11,1 years). Recurrent episodes of oral ulceration is the presenting manifestation in 78% of cases. Ocular involvement is the most disabling complication, being observed in 74% of cases. Of these, 80% present with bilateral involvement, with permanent sequelae in 52%. Cutaneous findings are observed in 82%, with pseudofolliculitis found in 62% of the total. Genital apthae were observed in 80% of cases. A positive pathergy test was displayed in 40%. Joint disturbances, not a diagnostic criterion, was the flrst clinical finding in 7% of all cases. As a whole, 85% of patients showed some joint involvement. The clinical diagnosis of BDis late (7,0 ± 7,5 years), but there is an inevitable delay in diagnosis of 4,0 ± 4,7years (range: 0-21), dueto the need to obtain and associate the necessary diagnostic criteria. Recurrent oral ulceration is afrequent flnding in family members of BD patients, being observed in 42% of first and second degree relatives. HIA B5 is found positive in 60% of cases, deflning a relative risk of 5. ln all B5 positive cases, in whom B51 was tested,100%, had a positive result.